Hospital Costs for Patients with Lower Extremity Cellulitis: A Retrospective Population-Based Study. (4th October 2017) - Challener, Douglas; Marcelin, Jasmine R; Visscher, Sue; Baddour, Larry M
Abstract: Background: Hospital admissions for non-purulent lower extremity cellulitis (NLEC) are common and can be prolonged and costly. Newer treatment options and prophylactic strategies should be expected to result in cost savings before implementation, but few studies have quantified the cost of conventional treatment. Methods: Using the Rochester Epidemiology Project, the incidence of NLEC in Olmsted County, MN in 2013 was 176.6 per 100, 000 persons. The subset of patients who required hospitalization for NLEC was determined. Hospital admissions were analyzed retrospectively using standardized cost analysis within several relevant categories. Results: Thirty-four patients had an average hospital length of stay of 4.7 days. The median total inpatient cost was $7, 341. The median cost per day was $2, 087. The bulk of this cost was related to room and board. Antibiotics for treatment of NLEC contributed a median cost of $75 per day of hospitalization, and laboratory or imaging tests cost $73 and $44, respectively, per day of hospitalization. Conclusion: Hospitalizations NLEC can be costly and prolonged, although antibiotic therapy was relatively inexpensive as compared with room and board. Therefore, newer treatment strategies should aim to reduce hospital length of stay and/or avoid inpatient admission to reduce cost. Disclosures: All authors: No reported disclosures.